"Yetzer" anthropologies in the "Apocalypse of Abraham" - Orlov, Andrei A. (Wissenschaftliche Untersuchungen zum Neuen Testament, 2021)
In this book, Andrei A. Orlov examines the imagery of "inclination" or yetzer found in the Apocalypse of Abraham. He argues that the text operates with several yetzer anthropologies, some of which are reminiscent of early biblical models, while others are similar to later rabbinic notions. Although the author focuses on the traditions found in the Apocalypse of Abraham, he also treats the evolution of the yetzer symbolism in its full historical and interpretive complexity through a broad variety of Jewish and Christian sources, from the creational narratives of the Hebrew Bible to later rabbinic testimonies. He further argues that a close analysis of the yetzer anthropologies found in the Apocalypse of Abraham challenges previous scholarly hypotheses that yetzer was only sexualized and gendered for the first time in the post-Amoraic sources